An insight of Marxist-Feminism in Thomas Hardy's Tess of the D'Urbervilles - Lee, Agnes Yun Ing; Babaee, Ruzbeh; Sedehi, Kamelia Talebian (Universiti Putra Malaysia Press, 2016)
Marxist-Feminism highlights the unjustifiable inequality faced by the working class citizen. The effect is especially evidently shown on women who have been subjugated and oppressed in so many ways by men. This study addresses the issues of subjugation and subordination faced by Tess, the Victorian woman, in Thomas Hardy’s Tess of the D’Urbervilles. The impact of cultural hegemony is carefully structured and presented by Marxist-Feminism. Such constructed ideology is brilliantly created to show the misleading superiority of men over women. The huge influence of Capitalism in the 19th Century is shown through the treatment women received in both public and private spheres. The active enrolments of women as Productive and Reproductive labours go unrecognised. Textual evidences are extracted to facilitate, support, and solidify the purpose of study.